Identification of Pathogenic Bacteria in Liquid Waste from "X" Hospital in Kediri City - Tri Ana Mulyati; Fery Eko Pujiono; Reza Alrayan; Binti Mu’arofah (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2024)
Introdiction: Hospitals can not only be a place for people to seek treatment, but they can also get diseases, especially infectious diseases. One source of the spread of infectious diseases comes from hospital waste, so proper waste processing is needed. Hospital wastewater contains many pathogenic bacteria such as Enterobacter cloacae, Bacillus sp., Kluyvera sp., Enterobacter sakazaki, Klebsiella oxytoca and E.coli. This makes it necessary to manage hospital wastewater to prevent the spread of disease, especially by pathogenic bacteria. On the other hand, research is still needed on the specific types of bacteria found in wastewater, including hospitals in Kediri City. Aims: to determine the types of pathogenic bacteria at the "X" hospital in Kediri City. Result: the density of bacteria in the bottom waste was greater than in the top and middle parts, with an average of 1,830 bacteria/100 ml. The results of the identification test showed that pathogenic bacteria contained in the waste from hospital "X" in Kediri City included Klebsiella (25%), E.coli (50%) and Pseudomonas (25%). Conclusion: The waste from "X" Hospital Kediri City contains three types of pathogenic bacteria: Klebsiella, E. coli, and Pseudomonas.